Laparoscopic Approach Criteria in Perforated Gastro-Duodenal Ulcers with Diffuse Peritonitis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article presents a comparative analysis of laparoscopic versus open surgery in patients with perforated gastric and duodenal ulcers complicated by diffuse peritonitis. Based on data from 114 patients (59 laparoscopic, 55 open), criteria for selecting surgical approach were identified, including hemodynamic stability, time from perforation, severity of peritonitis, and ulcer size. The study found that, when applied according to defined criteria, laparoscopic repair significantly reduced postoperative complications, accelerated recovery, and achieved comparable mortality rates. The results support the feasibility and safety of laparoscopic intervention in stable patients even in the presence of diffuse peritonitis.